KENYAMANAN TERMAL PADA PENGHUNI RUMAH PANGGUNG VERNAKULAR SUKU REJANG - Panji Anom Ramawangsa; Atik Prihatiningrum (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2024)
Abstract: The house is a basic human need to survive and improve the physical and psychological characteristics of its inhabitants. The stilt house is one form of residential construction that has developed in various remote areas. Seeing the problems of existing conditions, the purpose of this study was to determine the performance of the facade cladding on several research samples using the simulation method. The method used is a quantitative method by collecting data on temperature, humidity and wind speed from ventilation openings, windows and doors. Data collection was carried out for 2 weeks in August 2022 with detailed measurements for 1 (one) day at 07.00, 12.00 and 17.00. For the Predicted Mean Vote (PMV) and Standard Effective Temperature (SET) values using the CBE Thermal Comfort Tool, which can be accessed online. Based on the results obtained, the two houses on stilts of the Rejang tribe in Gunung Alam Village have different opening capability values that affect the quality of lighting, ventilation, humidity, and comfort that enter the residential building. It is also known that clothing and activities of occupants' movements in the house affect the quality of thermal comfort of the occupants' bodies, therefore movement in the house creates a neutral and comfortable feeling.Keyword: CBE, PMV, SET, stilt house, vernacularÂ Abstrak: Rumah merupakan kebutuhan pokok manusia untuk bertahan hidup dan meningkatkan sifat fisik dan psikis penghuninya. Rumah panggung merupakan salah satu bentuk konstruksi perumahan yang berkembang di berbagai daerah terpencil. Melihat permasalahan kondisi eksisting, maka tujuan penelitian ini adalah untuk mengetahui kinerja cladding fasad pada beberapa sampel penelitian dengan menggunakan metode simulasi. Metode yang digunakan adalah metode kuantitatif dengan mengumpulkan data suhu, kelembaban dan kecepatan angin dari bukaan ventilasi, jendela dan pintu. Pengumpulan data dilakukan selama 2 minggu pada bulan Agustus 2022 dengan rincian pengukuran selama 1 (satu) hari pada pukul 07.00, 12.00 dan 17.00. Untuk nilai Predicted Mean Vote (PMV) dan Standard Effective Temperature (SET) menggunakan CBE Thermal Comfort Tool yang dapat diakses secara online. Berdasarkan hasil yang diperoleh, kedua rumah panggung suku Rejang di Desa Gunung Alam mempunyai nilai kemampuan bukaan yang berbeda sehingga mempengaruhi kualitas penerangan, ventilasi, kelembapan, dan kenyamanan yang masuk ke dalam bangunan tempat tinggal. Diketahui juga bahwa pakaian dan aktivitas pergerakan penghuni dalam rumah mempengaruhi kualitas kenyamanan termal tubuh penghuninya, oleh karena itu pergerakan dalam rumah menimbulkan perasaan netral dan nyaman.Kata Kunci: CBE, PMV, SET, rumah panggung, vernakular